KEBERFUNGSIAN KELUARGA BURUH WANITA PLASMA INDUSTRI BULU MATA PALSU DI DESA GRANTUNG KECAMATAN KARANGMONCOL KABUPATEN PURBALINGGA - Wahyu Syabani Anistiarini; Theresia Martina Marwanti; Wawan Heryana (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2021)
The false eyelash industry in Purbalingga has penetrated international market and become an import commodity, so entrepreneurs innovate to expand their business with industrial plasma systems. Workers from the plasma of the industry almost entirely are women who have been family and are on the line of poverty, this is encouraging to the emergence of the problem of family functioning one of them in the village Grantung. This research aims to obtain a empirical overview of 1) the characteristics of respondents; 2) connection aspects; 3) asset aspect; and 4) environmental aspects. This research uses a descriptive method with a quantitative approach. Determination of the sample number of respondents using the survey technique is the entire population of 25 women laborers plasma false eyelash industry. The data collection techniques used are 1) questionnaires and 2) documentation studies. The results showed that the functioning aspect of the respondent family was in a less good category – quite well, with the lowest aspect being the connection aspect having a score of 531. While the other aspect, the asset aspect has a score of 733, the relationship aspect has a score of 715, and the environmental aspect has a score of 562. However, the low functioning of the respondent's family is due to the low level of education and skill and the absence of the Assembly that advocates for the welfare of respondents. Therefore, to address the problem, researchers proposed the program “Perhimpunan Srikandi Perwira dalam Peningkatan Keberfungsian Keluarga Buruh Wanita Plasma Industri Bulu Mata Palsu di Desa Grantung Kecamatan Karangmoncol Kabupaten Purbalingga”, which aims to improve the functioning of the family and welfare workers of women Plasma industry false eyelashes.